Bankruptcy and its enforcement: the effect of amendment in bankruptcy act 2003 / Mohd Firdaus Saleh and Md Azrin Rosly - Saleh, Mohd Firdaus; Rosly, Md Azrin (2008)
The main objective for this Honours Project Paper is to unearth the effect of the amendment on Bankruptcy Act that took place in the year 2003. For the purpose of this research, we will be focusing on three amendments that brought an impact to Malaysian bankruptcy law. Our research will be focusing on section 5 (3) that deals on the issue of social guarantor, section 5 (1) (A) that deals with the amount of debt and lastly section 33 A that deals with the power of the Director General of Insolvency to discharge a bankrupt. From these amendments, our research is hoped to discover the amendments advantages and disadvantages. Apart from that, our research will analyze the effectiveness of these amendments whether it has achieved its objective or not. We also will enlighten our readers with the opinion and suggestion from the bankruptcy legal experts in Malaysia. Our research also will provides the comparison with our bankruptcy law and Singapore bankruptcy law to analyzed how effective the law of bankruptcy in Malaysia compared to Singapore. As a whole, our research is hoped to overcome the disadvantages of the Bankruptcy Act amendments that took place in 2003 and to provide solution and suggestion to overcome it.